Green finance in Singapore: Barriers and solutions - Chang Youngho (Asian Development Bank Institute (ADBI), 2019)
Green finance, or the issuance of green bonds, has gained strong momentum around the world. Some Asian countries such as the People's Republic of China and Japan are very active in green finance. This study reviews how green finance in Singapore is working, examines existing barriers, and suggests some solutions. Singapore, a well-established financial hub in Asia, aims to be a hub for green finance in Asia. The Monetary Authority of Singapore (MAS), the central bank of Singapore, has formed a network with seven other central banks in the world called the Central Banks and Supervisors Network for Greening Financial System, which intends to promote sharing of experience and best practices in green finance with other countries. Along with forming the network, the MAS has established a Green Bond Grant scheme to promote and ensure the issuance of green bonds in Singapore. In parallel, the Association of Banks in Singapore published Guidelines on Responsible Financing to promote and support environmental, social, and governance (ESG) disclosures. The Singapore Exchange asks its member firms to strictly comply with the ESG disclosures. At an individual firm level in Singapore, City Development Limited (CDL), a real estate development company, and Development Bank of Singapore Limited (DBS), a commercial bank, issued Singapore's first and second green bonds in 2017. The proceeds of the CDL green bond are allocated to finance retrofitting and upgrading of a commercial building in Singapore, while the proceeds of the DBS green bond are to be invested in renewable energy and climate change adaptation, among other uses. How successful the two green bonds are in meeting their pronounced goals and how well and effectively they contribute to the diffusion of renewable energy remains to be seen.
Keywords: G18; G28; G38; 330; green finance; green bond grant scheme; guidelines of responsible financing; CDL green bond; DBS green bond